ISO27001 in a Windows environment : the best practice handbook for a Microsoft Windows environment - Honan, Brian (IT Governance, 2010)
Ideal for project managers, IT and security staff, this book plugs the gap in current guidance literature for ISO27001. ISO27001, the information security management standard (ISMS), is providing a significant challenge for many organisations. One of the key areas of confusion is the relationship between the ISO27001 ISMS project manager and those responsible for implementing the technical controls.